Alexithymia and brain gray matter volumes in a general population sample. Issue 12 (1st August 2014) - Grabe, Hans Jörgen; Wittfeld, Katharina; Hegenscheid, Katrin; Hosten, Norbert; Lotze, Martin; Janowitz, Deborah; Völzke, Henry; John, Ulrich; Barnow, Sven; Freyberger, Harald J.
Abstract Alexithymia is perceived as a personality construct involving deficits in the cognitive processing of emotion. Brain areas that process emotions might be structurally altered in affected people. Subjects from the Study of Health in Pomerania who underwent whole body magnetic resonance imaging were investigated. After quality control procedures 2, 589 subjects with Toronto Alexithymia Scale 20 (TAS‐20) data and interview‐based information on major depressive disorder (MDD) were available. After exclusion of study participants who were older than 65 years or had MDD in their lifetime, 1, 685 subjects were included in the voxel‐based morphometric (VBM 8) analyses. In whole‐brain analyses, the TAS‐20 total score was associated with less gray matter (GM) volumes of the bilateral dorsal anterior cingulate cortex (dACC). The TAS‐20 factor scale difficulty identifying feelings (DIF) was associated with less GM volume in three clusters: dACC, left middle and inferior temporal gyrus, left fusiform gyrus and cerebellum. The lower GM volume in the left fusiform gyrus was specific for females. Absolute GM volume analyses also revealed associations between the factor scales difficulty describing feelings, external orientated thinking and the dACC. Adjustment for current symptoms of anxiety and depression did not change the effects sizes substantially. In conclusion, lower GM volume in the dACC represents the major structural correlate of alexithymia. Associations with DIF suggest a prominent involvement of left temporal areas. These areas represent language and semantic processing and might be involved in the cognitive processing of emotions and the conscious identification of feelings. Hum Brain Mapp 35:5932–5945, 2014. © 2014 Wiley Periodicals, Inc.